2018
DOI: 10.1111/cga.12277
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a patient with classical Ehlers‐Danlos syndrome due to a 9q34 duplication affecting COL5A1

Abstract: Ehlers-Danlos syndrome classical type is a connective tissue disorder characterized by skin hyperextensibility, atrophic scarring, and joint hypermobility. The condition typically results from mutations in COL5A1 or COL5A2 leading to the functional haploinsufficiency. Here, we report of a 24-year-old male with mild intellectual disability, dysmorphic features, and a phenotype consistent with Ehlers-Danlos syndrome classical type. A copy number variant-calling algorithm from panel sequencing data identified the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…We found that NGS can detect the CNV that were already identified in the microarray analysis (data not shown). We have shown previously that it is possible to detect CNV using NGS but not aCGH, at the exon‐level . The overall diagnostic rate of Group A was 39% (39 cases).…”
Section: Resultsmentioning
confidence: 95%
“…We found that NGS can detect the CNV that were already identified in the microarray analysis (data not shown). We have shown previously that it is possible to detect CNV using NGS but not aCGH, at the exon‐level . The overall diagnostic rate of Group A was 39% (39 cases).…”
Section: Resultsmentioning
confidence: 95%
“…In Ritelli et al, an investigation among 40 patients, one of the duplications of exons 1-11 in COL5A1 was detected (probe for COL5A2 were not available) [16]. In the investigation of Kuroda et al, cEDS patients with alterations in COL5A1 (deletion of exons 2-11 and duplication of exons 12-65) were determined identified by aCGH [17]. All patients analyzed in the present study need wider diagnostics because we cannot exclude DNA changes other than those detected by NGS.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in an X-linked gene, NEXMIF (neurite extension and migration factor, also known as KIDLIA, KIAA2022, or Xpn) were first discovered in several males with ASD, intellectual disability, and other co-morbidities (Cantagrel et al, 2004;Van Maldergem et al, 2013). Since then, several studies have reported additional ASD individuals with mutations or deletions in the NEXMIF gene (Lim et al, 2013;Iossifov et al, 2014;Charzewska et al, 2015;Kuroda et al, 2015;De Lange et al, 2016;Farach and Northrup, 2016;Webster et al, 2017;Yuen et al, 2017;Lambert et al, 2018;Lorenzo et al, 2018;Panda et al, 2020;Stamberger et al, 2020;Wang et al, 2020). NEXMIF is now recognized as a Category 1 gene in the Simons Foundation Autism Research Initiative (SFARI) database, further implicating it as an ASD-risk gene.…”
Section: Introductionmentioning
confidence: 99%